A review of sustainable cattle genetic improvement in the Peruvian Highlands - Alvarez García, Wuesley Yusmein (2025)
Cattle breeding in the highlands of Peru is an important economic activity at the level of the entire rural extension, because it serves as an economic reserve for rural families and forms an integral part of the agri cultural producer’s culture. This review aimed to provide a literature- and research-based approach to the fundamental aspects of a national genetic improvement plan, emphasising the efficacy of using a bovine germplasm of high genetic quality as an initiative to implement genetic improvement programmes. The concepts to be implemented in national livestock farming include high yield, feed conversion efficiency, and minimum greenhouse gas emissions. The use of a dual-purpose germplasm to maximise the usefulness of livestock farmers and the implementation of improvement programmes, with the expectation of achieving a differential increase in genetic merit, were also considered. In addition to aspects related to milk and carcase quality, there is a terri torial approach, such as the case of breeds that adapt to terminal crossbreeding and consider reproductive as pects. One of the final aspects considered is the conservation and valuation of local animals within conservation and improvement plans owing to their resistance and adaptation to temperature and altitude conditions